Communication Strategies of the Multipurpose Syari'ah Cooperative of Musi Sejahtera Palembang in Improving the Welfare of the Members - Muhammad Taufik (Medina-te : Jurnal Studi Islam, 2020)
The aim of this research was to identify the all-round business syari'ah cooperative development program, "Musi Sejahtera Palembang”. The research method used in this research was qualitative research method. The research data were obtained through observation, interviews and documentation. Furthermore, the data obtained were assessed by descriptive-analytic technique and will eventually be concluded as the final outcome of this study. From the results of the research it can be concluded that the communication strategy of the Syari'ah Serba Usaha Musi Sejahtera Palembang cooperative in improving the welfare of its members was carried out through personal individual and communication. Meanwhile, the factor supporting the implementation of cooperative activities is as follows: working good cooperation with various stakeholders as well as facilities and infrastructure support. Meanwhile the inhibiting factors are as follows: 1) the human resources were less qualified; 2) lack of Board to manage the membership of a cooperative; 3) lack of awareness ofthe members of Syari’ah Serba Usaha Musi Sejahtera Palembang Cooperative in participating actively and the system management ofSyari’ah Serba Usaha Musi Sejahtera Palembang was not doing well.